2014
DOI: 10.1161/hypertensionaha.114.04147
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal CD8 + T Cells Play a Critical Role in the Development of Hypertension

Abstract: Recent studies have emphasized a role of adaptive immunity, and particularly T cells, in the genesis of hypertension. We sought to determine the T cell subtypes that contribute to hypertension and renal inflammation in angiotensin II-induced hypertension. Using T cell receptor (TCR) spectratyping to examine TCR usage we demonstrated that CD8+ cells, but not CD4+ cells, in the kidney exhibited altered TCR transcript lengths in Vβ3, 8.1 and 17 families in response to angiotensin II-induced hypertension. Clonalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
173
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(190 citation statements)
references
References 34 publications
5
173
1
3
Order By: Relevance
“…This in turn could promote sodium and volume retention. 73 It should be recognized that mice lacking CD4 + cells also lack Tregs and this perhaps predisposes these animals to worsened hypertension.…”
Section: /2mentioning
confidence: 99%
“…This in turn could promote sodium and volume retention. 73 It should be recognized that mice lacking CD4 + cells also lack Tregs and this perhaps predisposes these animals to worsened hypertension.…”
Section: /2mentioning
confidence: 99%
“…Indeed, it has been recently reported that oligoclonal CD8 ? T cells play a crucial role in the development of hypertension in a mouse model [83]. In addition, a recent study has identified oxidatively modified proteins by highly reactive c-ketoaldehydes (isoketals) as CD8 ?…”
Section: Senescent T Cells In Essential Hypertensionmentioning
confidence: 99%
“…1-3 Mice and rats lacking T-lymphocytes exhibit blunted hypertensive responses to experimental hypertension, restored by adoptive transfer of T-cells. 4-6 Trott et al recently provided evidence that a population of CD8 + T-cells, not CD4 + T-cells, play a critical role in the development Ang II infusion hypertension. 6 Recent evidence also indicates that isoketal-modified proteins are formed in dendritic cells, and that these are recognized as non-self and promote T cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…4-6 Trott et al recently provided evidence that a population of CD8 + T-cells, not CD4 + T-cells, play a critical role in the development Ang II infusion hypertension. 6 Recent evidence also indicates that isoketal-modified proteins are formed in dendritic cells, and that these are recognized as non-self and promote T cell activation. 7 In the kidney, cytokines released from these cells activate local production of angiotensin II (AngII), even when systemic levels of AngII are low.…”
Section: Introductionmentioning
confidence: 99%